Al-QUR'AN LITERACY: CONCEPTIONS OF METAPHORICAL THINKING IN THE HOLY QURAN - Aziz, Husein; Hikmawati, Masna (Proceedings of International Conference on Islamic Civilization and Humanities, 2024)
This research is intended to answer the problem, how the al-Qur’an al Karim expresses metaphorical thinking and what its uses and benefits are. Any discourse uses metaphorical expressions to produce meaning. Some of the vocabulary in metaphorical expressions refers to denotative meaning and some refers to connotative meaning. This article aims to find out how the language of the Koran conveys thoughts, thoughts and ideas. This research focuses on the problem of what metaphors are and what their significance is in conveying thoughts both in the fields of science and religious knowledge. To answer this question, this research uses a qualitative descriptive method with linguistic analysis and a library research approach. From the results of this research, it is concluded that (a) metaphor is a shift from original, denotative meaning to connotative meaning, metaphor is needed because language vocabulary is limited while meaning is unlimited (b.) metaphor is used to convey thoughts both related to science and other fields. religious knowledge and make the intended thoughts appear more effective, clearer, easier to understand and more beautiful. This is so because it appears in a sensory, lively, active, imaginative, communicative and persuasive form.